Long way to go: Progress of orphan drug accessibility in China from 2017 to 2022 - Liu, Jia; Yu, Yue; Zhong, Mingkang; Ma, Chunlai; Shao, Rong (Frontiers in Pharmacology, 2023)
Over 400 million patients worldwide suffer from rare diseases. Access to orphan drugs is, therefore, crucial for this population. China has been actively working on improving orphan drug accessibility in the past decades, especially since 2018 when the First National List of Rare Diseases was announced. This study aimed to evaluate the current status of orphan drug accessibility in China regarding availability, daily cost, and affordability. Market availability of orphan drugs in China was based on their approval status in China up to May 2022. Information on drug availability in hospitals and the cost of each drug from 2017–2021 was obtained from the database of the Science and Technology Development Center of the Chinese Pharmaceutical Association. Affordability was assessed by comparing the disposable daily income per capita to the cost of the defined daily dose of each drug. Market availability rate was 44.3% by May 2022, and the average delay in drug approval in China compared to its approval in the United States of America was 5.9±6.07 years. Drug availability in hospitals showed an upward trend, with availability in tertiary hospitals significantly higher than in secondary hospitals ( 20%, p<0.0001). The eastern area was significantly higher in availability from 2019 onwards. Fifty-eight percent of the orphan drugs were still considered to have very low availability (<30%). The national median cost of the defined daily dose across all available orphan drugs had increased to 254.97 RMB in 2021. Only 34.98% of the orphan drugs were considered affordable when compared with the national average disposable daily income in 2021, and drug affordability decreased during the past five years. Changes in orphan drug regulations in China have enabled progress regarding the drugs’ market availability, but the current status of drug availability at hospitals, drug cost, and affordability were not optimal. Legislation for encouraging domestic drug development and novel payment schemes for high-value drugs are essential to further improve the availability and cost burden of orphan drugs in China.